SIMULATION OF FLOW THROUGH AN EQUISPACED IN-LINE CYLINDER IN OPEN CHANNELS - Al-Osmy, Sanaa A. Talab; Mulahasan, Saad; Fartosy, Sabah Hassan Lafta (Journal of Applied Engineering Science, 2022)
In this work, a numerical simulation using Computation Fluid Dynamics technique was used to investigate the flow properties and turbulence characteristics through flow of one-line cylinder in an open channel with uniform flow conditions. A two-dimensional turbulence model was applied using ANSYS. Flow properties were investigated against varying cylinder diameters that forms a one-line cylinder physical model and varying flow rates. Three cylinders diameters D were used (5.0 cm, 2.5 cm and 1.25 cm) and located at 12.5 cm apart along the flume centre-line. Spatial distributions of mean-stream-wise velocity, pressure, turbulent kinetic energy, and eddy viscosity were estimated. Results showed symmetrical distribution of flow velocity, turbulence eddy, and turbulent kinetic energy along the one-line cylinder for the largest cylinder diameter. Vortex shedding patterns were well predicted by the numerical simulation behind the cylinders. Different configurations of vortices distribution behind the cylinders were recorded for the diameters of 1.25 cm and 2.5 cm. The flow pattern difference between the largest diameter (5 cm) and the small diameters (2.5 cm and 1.25 cm) was leaded to the strong overlap for the vortices in the wake for the lined cylinders with the large diameter in comparison to the other diameters. Consequently, this study is investigated the different diameter sizes of a one-line cylinder with the same spacing between them on the flow pattern along the channel.
Keywords: simulation, one-line cylinders, ANSYS, turbulent flow, vortex patterns